2016
DOI: 10.1177/1103308816640699
|View full text |Cite
|
Sign up to set email alerts
|

Wendy, Peter and the Lost Boys—The Gendered Discourses of Welfare Service Practitioners and Their Young Clients

Abstract: The article examines the discourses related to gender in interviews with welfare service practitioners and their young, 18-to 29-year-old clients using 'boy discourse' as an analytical framework and J. M. Barrie's story of Peter Pan as a metaphorical framework. Those beyond the reach of the welfare services are referred to by the practitioners as 'lost young people'. Some practitioners see young men in particular as poor creatures, unable to achieve anything without a girlfriend, whose task is to get these Pet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, NEET young women may be invisible in this context because the discourses that the NEET concept is understood in relation to mainly concern boys; additionally, owing to traditional and socially sanctioned roles for women as homemakers and carers, NEET young women do not constitute a violation of social aesthetics in the same way that NEET young men do. However, that they are not mentioned in interviews does not necessarily mean that they do not exist (Berg and Aaltonen, 2016).…”
Section: Three Levels Of Meaningmentioning
confidence: 97%
“…For example, NEET young women may be invisible in this context because the discourses that the NEET concept is understood in relation to mainly concern boys; additionally, owing to traditional and socially sanctioned roles for women as homemakers and carers, NEET young women do not constitute a violation of social aesthetics in the same way that NEET young men do. However, that they are not mentioned in interviews does not necessarily mean that they do not exist (Berg and Aaltonen, 2016).…”
Section: Three Levels Of Meaningmentioning
confidence: 97%
“…Prominent in the discussions is the subject position of the 'lost' boy 8 or man who needs guidance in engaging in a post-#MeToo world. Berg and Aaltonen (2017) contend that this notion of young boys requiring guidance can be found in social welfare approaches to supporting young men, whereby many are described as 'lost' and unable to cope without (feminine) guidance. Similar ideas can be found in mythopoetic movements, which encouraged men to seek out their natural inner warrior at overnight meetings and camps with other men (Singleton, 2004), often led by a leader or in the case of the Promise Keepers, a Christian saviour who could lead men to the right path.…”
Section: 'Lost' Boys and Becoming 'Men'mentioning
confidence: 99%
“…These groups of Finnish youth have been framed in Finnish discourses as 'socially excluded', those who need to be brought back to mainstream society through work or education. The classed logic of youth activation was identified by Berg and Aaltonen (2017) in their study on the majority Finnish youth position in welfare services, which showed that few young people attending youth activation were from upper/middle-class positions, who were aiming for higher education. The classed and racialised logic of employment was reflected in the counsellors' offerings of unpaid work placements in grocery stores and retail shops as well as educational opportunities in construction, logistics, bus driving and care work.…”
Section: Classifying the Unemployed In Finlandmentioning
confidence: 99%
“…Due to the lack of space only several ethnographic cases have been selected to illustrate my argument. However, these examples reflect the general logic of approaching young, unemployed working-class and racialised men as being at a higher risk of social exclusion, being less responsible job-seekers and in need of activation in order to get 'on the right track' (see also Berg and Aaltonen, 2017). The feeling of suspicion and distrust dominated the relations between young men and the counsellors.…”
Section: Controlling 'Disobedient' Migrant Masculinitiesmentioning
confidence: 99%
See 1 more Smart Citation